ANALISIS WACANA ‘WHAT’S UP WITH MONAS?’ DENGAN PENDEKATAN LINGUISTIK SISTEMIK FUNGSIONAL. - Atsani Wulansari (TRANSFORMATIKA, 2016)
The aims of this research are (1) to analyze metafunction in the discourse, (2) to analyze interdependent and logico semantic meaning, and (3) to analyze the nominal group in the discourse. This research was descriptive qualitative research. The source of the data in this research was the discourse entitled What’s up with Monas?. The data was analyzed by using Systemic Functional Linguistic approach. This research found 19 clause of indicative-declarative in the discourse. Interpersonally, the writer of this discourse plays his role to give information to the reader. Ideationally, the researcher found that material process dominated the discourse. The circumstance that found was circumstance of time and place. Textually, unmarked topical theme was dominated the discourse. From interdependent and logico semantic relationship, the researcher found that clause complex appeared more often than simple clauses. This relationship influences the style of the discourse. Moreover, in nominal group, there were 8 nominal groups with classifier, 3 nominal groups with epithet and 9 nominal groups with qualifier.  From the analysis above, we can conclude that the discourse in this research include to news item. Key words: Discourse Analysis, Systemic Functional Linguistic, Genre